2022
DOI: 10.1186/s12864-022-09039-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transcriptomic analysis reveals a coordinated mechanism activated in response to cold acclimation in common vetch (Vicia sativa L.)

Abstract: Background Due to its strong abiotic stress tolerance, common vetch is widely cultivated as a green manure and forage crop in grass and crop rotation systems. The comprehensive molecular mechanisms activated in common vetch during cold adaptation remain unknown. Results We investigated physiological responses and transcriptome profiles of cold-sensitive (Lanjian No. 1) and cold-tolerant (Lanjian No. 3) cultivars during cold acclimation to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Salinity leads to the accumulation of Na + and ionic toxicity in common vetch [ 22 , 65 ]. The intracellular Na + and K + ion balance plays a crucial role in plant salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salinity leads to the accumulation of Na + and ionic toxicity in common vetch [ 22 , 65 ]. The intracellular Na + and K + ion balance plays a crucial role in plant salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…4.4. Na + and K + Transport and ROS Scavenging Were Associated with the Differential Salt Tolerance between the Two Lines Salinity leads to the accumulation of Na + and ionic toxicity in common vetch [22,65]. The intracellular Na + and K + ion balance plays a crucial role in plant salt tolerance.…”
Section: The Carbohydrate and Energy Metabolisms Were Associated With...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cold is a common abiotic stress that has become a major environmental factor affecting plant life cycle and geographic distribution as well as crop yields by influencing plant growth and development [2]. The immense impact of cold stress on global agricultural productivity is undeniable, with cold damage costing approximately $2 billion annually which includes about 13 million hectares of rice each year [3,4]. Therefore, understanding the cold resistance mechanisms of plants to improve their cold tolerance is essential to maintain sustainable agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in the recent years, transcriptome studies have provided a new perspective for research on the plant response to cold stress [3,7,17]. A previous study reported that the plant circadian pathway was crucial for the response of Helictotrichon virescens to cold stress; the expression of DEGs encoding LHY and HY5 were strongly up-regulated during cold stress [7].…”
Section: Introductionmentioning
confidence: 99%